Pictorial Guide for the Identification of Rice Diseases and Pests - Castilla, Nancy; Carvajal, Raphael Gabriel; Almazan, Ma. Liberty; Manalo, Nolan (International Rice Research Institute, 2025)
The first version of pictorial guide for the identification of rice diseases and pests was developed as a handy reference tool for farmers and extension workers. It covers 22 rice diseases, 19 insect pests, and the root-knot nematode. The booklet features high-quality photographs along with descriptions of distinguishing characteristics and symptoms of major diseases and insect pests. These are organized first by type of pest (disease or insect) and then by the affected plant part. Written in simple English, the guide is designed to be user-friendly and easy to understand. The guide is currently being translated to Hiligaynon, a language spoken in Western Visayas region and parts of Mindanao.